New insight into LSD1 function in human cortical neurogenesis. Issue 1 (1st January 2016) - Hirano, Kazumi; Namihira, Masakazu
ABSTRACT: The cerebral cortex of primates has evolved massively and intricately in comparison to that of other species. Accumulating evidence indicates that this is caused by changes in cell biological features of neural stem cells (NSCs), which differentiate into neurons and glial cells during development. The fate of NSCs during rodent cortical development is stringently regulated by epigenetic factors, such as histone modification enzymes, but the role of these factors in human corticogenesis is largely unknown. We have recently discovered that a lysine-specific demethylase 1 (LSD1), which catalyzes the demethylation of methyl groups in the histone tail, plays a unique role in human fetal NSCs (hfNSCs). We show that, unlike the role previously reported in mice, LSD1 in hfNSCs is necessary for neuronal differentiation and controls the expression of HEYL, one of the NOTCH target genes, by modulating the methylation level of histones on its promoter region. Interestingly, LSD1-regulation of Heyl expression is not observed in mouse NSCs. Furthermore, we first demonstrated that HEYL is able to maintain the undifferentiated state of hfNSCs. Our findings provide a new insight indicating that LSD1 may be a key player in the development and characterization of the evolved cerebral cortex.